Ekranisasi Alur Dalam Novel Dan Film Howl’s Moving Castle - Gianita, Adiya (PT. Alahyan Publisher Sukabumi, 2023)
Ecranization is a process of appointing a novel into a film. Therefore, this study aims to discuss the process of ecranization of Howl's Moving Castle novel by Diana Wynne Jones, where there is a process of change in the plot in the form of reduction, addition, and variation. This research is a qualitative research using comparative descriptive research method. The data sources are from the novel Howl's Moving Castle by Diana Wynne Jones and from the film Howl's Moving Castle. In addition, this research uses an intertextual approach in understanding and comparing plots in the novel Howl's Moving Castle by Diana Wynne Jones and the film Howl's Moving Castle. In this study there were changes to the plot in the form of 5 reduction processes, 1 addition process, and 2 variation processes.